Determinants of Higher-Risk Sexual Behavior in Some Selected African Countries - Adikwor Ewoenam Puplampu; Seth Afagbedzi; Samuel Dery; Dzifa Adimle Puplampu; Chris Guure (Scientifica)
Background. Although higher-risk sexual behavior (H-RSB) is a major contributor to the rapid rising rate of new HIV infections, there exists paucity of comprehensive evidence across the sub-Saharan African region. The purpose of this study was to determine the prevalence of H-RSB and its determinants across sub-Saharan Africa to inform policy. Method. Data were obtained from the Demographic and Health Survey (DHS) of ten sub-Saharan African (SSA) countries with their three most current DHS surveys from 2000 to 2016. Only participants who ever had sexual encounters in their lifetime were included in the study. Weighted adjusted Cox regression with robust variance and constant time was used to investigate disparities of H-RSB among the ten SSA countries. Relationships between sociodemographic, socioeconomic, knowledge, mass media, and H-RSB were investigated. Results. The trend and prevalence of higher-risk sexual behavior show that Lesotho experienced a decreasing trend of the prevalence of H-RSB from 8.92 in period one to 6.42 in period three. Ghana experienced a marginal increase from 6.22 in period one to 6.76 in period two and then to 6.43 in the third period. However, Malawi, Zambia, and Zimbabwe obtained a marginal increasing trend in the prevalence of H-RSB from period one to three: 2.75 to 3.74, 4.33 to 6.24, and 6.11 to 7.99, respectively. Meanwhile, the prevalence of H-RSB in Namibia and Uganda decreased in period two to 1.84 and 5.76 but increased in period three to 2.01 and 6.83, respectively. Generally, determinants of H-RSB among the countries include age, sex, religious affiliation, marital status, educational level, employment status, economic status, age at first sex, and status of circumcision. Conclusion. Trend of relatively high prevalence of H-RSB has been found across majority of the countries with key sociodemographic factors influencing H-RSB. Therefore, different targeted interventional approaches are needed in all the countries to help reduce H-RSB and the overall HIV incidence. If issues regarding sexual behavior and sexual health are not addressed adequately, H-RSB can negate all the appreciable efforts aimed at ending the HIV pandemic by 2030.